2012
DOI: 10.1007/s11670-012-0036-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of serum vascular endothelial growth factor on prognosis in patients with unresectable hepatocellular carcinoma after transarterial chemoembolization

Abstract: Objective: To investigate the expression level of serum vascular endothelial growth factor (VEGF) in patients with unresectable hepatocellular carcinoma (HCC) and its relationship with the clinicopathological characteristics, and to assess the impact of serum VEGF as a predictive factor for HCC prognosis during transarterial chemoembolization (TACE) treatments.Methods: Serum VEGF levels were measured using enzyme-linked immunosorbent assay (ELISA) in 60 random patients who underwent TACE or transarterial infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 34 publications
(37 reference statements)
1
14
0
Order By: Relevance
“… 11 13 Moreover, an increase in vascular endothelial growth factor (VEGF) levels has been reported in patients treated with TACE and to predict poor prognosis. 12 , 14 The use of sorafenib can significantly counteract the tyrosine kinase receptors VEGFR-2/3 and platelet-derived growth factor receptor (PDGFR)-b, which decreases the post-TACE VEGF and PDGF upregulation and further enhances the efficacy of TACE. 15 , 16 Besides, sorafenib combined with cytotoxic drug shows a synergism that sorafenib inhibits the Ras/Raf/MEK/ERK pathway, which will prevent activation of the multidrug resistance pathway that leads to the failure of chemotherapy in treating HCC.…”
Section: Introductionmentioning
confidence: 99%
“… 11 13 Moreover, an increase in vascular endothelial growth factor (VEGF) levels has been reported in patients treated with TACE and to predict poor prognosis. 12 , 14 The use of sorafenib can significantly counteract the tyrosine kinase receptors VEGFR-2/3 and platelet-derived growth factor receptor (PDGFR)-b, which decreases the post-TACE VEGF and PDGF upregulation and further enhances the efficacy of TACE. 15 , 16 Besides, sorafenib combined with cytotoxic drug shows a synergism that sorafenib inhibits the Ras/Raf/MEK/ERK pathway, which will prevent activation of the multidrug resistance pathway that leads to the failure of chemotherapy in treating HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that the VEGF family not only has a crucial impact on the tumorigenesis, development and invasion of many solid tumors such as gastrointestinal cancer, urinary cancer, nervous system tumors, but that VEGF signaling is also significant to the pathogenesis and prognosis of tumors in the blood and lymphatic system ( 8 ). VEGF-A is the ligand most involved in VEGFR-mediated angiogenesis and it can promote the differentiation of vascular progenitor cells into vascular endothelial cells ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Serum VEGF levels reflect both plasmatic and intra-platelet concentrations, and since plasma contains a substantially lower level of VEGF, platelets are the primary source of serum VEGF. Several studies were published focusing on the direct correlation between serum VEGF and HCC (Table 2) [36,56,57,58,59,60,61,62,63,64]. The ratio between serum VEGF and platelet count or platelet VEGF values alone were investigated in some studies on HCC, showing a direct correlation with tumor diameter [59], recurrence after local treatment [63], vascular invasion [56,64], and overall survival [56].…”
Section: The Connection Between Platelets and Vascular Endothelialmentioning
confidence: 99%
“…A recent meta-analysis based on 11 studies evaluating the correlation between serum VEGF level and survival in patients with HCC confirmed these data, showing that serum VEGF levels had an unfavorable impact on both disease-free (HR = 2.27, 95%CI = 1.55–2.98) and overall survival (HR = 1.88, 95%CI = 1.46–2.30) [61]. Overall, the increase in serum VEGF was a poor prognostic indicator in HCC patients undergoing several different treatments, such as radiotherapy, trans-arterial chemoembolization (TACE), resection, and liver transplantation [57,58,60,62,64].…”
Section: The Connection Between Platelets and Vascular Endothelialmentioning
confidence: 99%